Metastatic choroidal pulmonary biphasic blastoma as a unique single initial metastasis to the eye: a case report - Heba Mahjoub; Eleni K. Konstantinou; Huan M. Mills; Nora M. V. Laver; Jeffrey Chang (Journal of Medical Case Reports)
Abstract Background Choroidal metastasis is the most common intraocular malignancy in adults, commonly presenting in later stages of the disease and associated with poor prognosis. This is the first case to describe choroidal involvement as the sole initial metastasis of the rare biphasic pulmonary tumor. Case presentation A 42-year-old white male patient presented to the emergency department with 3 weeks of progressive temporal visual field loss in the left eye (oculus sinister) with slight discomfort to palpation. At the emergency department, he underwent computed tomography and computed tomography angiography of the brain to rule out a central nervous system etiology of his vision loss. The imaging demonstrated lentiform dependent hyperdense material with layering hypodensity within the medial aspect of the left globe, consistent with choroidal detachment. His prior medical history was significant for biphasic pulmonary blastoma cT2N2M0 stage IIIA involving the right lung, with extension into the superior vena cava, diagnosed 3 years prior to the current presentation. He was treated with chemoradiation and excision with complete response to therapy. Conclusion As the survival rates for cancer patients are increasing owing to better quality and more available treatments, choroidal metastasis may become more common. Early diagnosis and effective treatment of these lesions is crucial for better patient outcomes.